Interference of functional monomers with polymerization efficiency of adhesives. (11th February 2016) - Hanabusa, Masao; Yoshihara, Kumiko; Yoshida, Yasuhiro; Okihara, Takumi; Yamamoto, Takatsugu; Momoi, Yasuko; Van Meerbeek, Bart
Abstract : The degree of conversion (DC) of camphorquinone/amine‐based adhesives is affected by acidic functional monomers as a result of inactivation of the amine co‐initiator through an acid–base reaction. During bonding, functional monomers of self‐etch adhesives chemically interact with hydroxyapatite (HAp). Here, we tested in how far the latter interaction of functional monomers with HAp counteracts the expected reduction in DC of camphorquinone/amine‐based adhesives. The DC of three experimental adhesive formulations, containing either of the two functional monomers [10‐methacryloyloxydecyl dihydrogen phosphate (10‐MDP) or 4‐methacryloxyethyl trimellitic acid anhydride (4‐META)] or no functional monomer (no‐FM; control), was measured with and without HAp powder added to the adhesive formulations. Both the variables 'functional monomer' and 'HAp' were found to be significant, with the functional monomer reducing the DC and HAp counteracting this effect. It is concluded that the functional monomers 10‐MDP and 4‐META interfere with the polymerization efficiency of adhesives. This interference is less prominent in the presence of HAp, which would clinically correspond to when these two functional monomers of the adhesive simultaneously interact with HAp in tooth tissue.